Geochemical study on Impact of Tarball on Chendering Beach Kuala Terengganu, Malaysia. Issue 1 (1st November 2022) - Abidin, Z H Zainal; Azman, N I N; Shafiee, N S; Sulaiman, N; Khan, M M Ali
Abstract : Oil pollution is considered one of the main contributors to marine pollution. The threat that oil pollution poses to the marine environment is extremely dangerous to its ecosystem. The South China Sea is an important route for various activities, including fishing, recreational and marine activities, and oil and gas exploration. Tarballs are a common byproduct of oil spills, which arise when the sun, wind, and water break down the oil. Tarballs are clumps or blobs of oil and hydrocarbon that have been weathered and displaced from the main body of oil by ocean currents can be found along the shorelines of the Eastern, South China Sea, and Western, Selat Malacca coasts.. The beaches at Chendering in Kuala Terengganu, which face the South China Sea, are also affected by tarball pollution. The geochemical study of tar balls and surface sediments of Chendering area is located at Chendering beach coastal plain area, 103° 11' 09" E, 5° 16' 09" N. In this study, The Inductive Couple Plasma-Optimal Emission Spectroscopy (ICP-OES) was used to analyse 12 soil samples (contaminated with tarballs) for heavy metal components. The ICP-OES result shows that average concentrations of heavy metal of beach sediments display the following ascending pattern Cu < Pb < Ni < Cr < Zn < Mn with the value of range 0.100, 0.331, 0.633, 0.905 and 3.226 ppm respectively.